(untitled) (Bangladesh Journal of Medical Science, 2010)
Background: The study of ethnobotany relating to any tribe is in itself a very intricate or convoluted process. This paper documents the traditional knowledge of medicinal plants that are in used by the Jenu kuruba ethnic group of Karnataka state (South India). Methodology & Results: The present study was done through structured questionnaires in consultations with the tribal practitioners, patients and has resulted in the documentation of 20 medicinal plant species belonging to 17 families and 25 genera. For curing diverse form of ailments, the use of aboveground plant parts was higher (66.59%) than the underground plant parts (21.41%). Of the aboveground plant parts, leaf was used in the majority of cases (9%), followed by fruit (4%). Different underground plant forms such as root, tuber, rhizome, bulb and pseudo-bulb were also found to be in use by the Jenu kuruba tribe as a medicine. Altogether, 21 types of ailments have been reported to be cured by using these 20 medicinal plants species. Perceived efficacy have given. Conclusions: The study thus underlines the potentials of the ethnobotanical research and the need for the documentation of traditional ecological knowledge pertaining to the medicinal plant utilization for the greater benefit of mankind. This paper is based on the field exploration conducted in Karnataka (South India). Keywords: Jenu kuruba; Ethnic group; Medicinal plants; Diseases. DOI: 10.3329/bjms.v9i3.6479 Bangladesh Journal of Medical Science Vol.09 No.3 July 2010, pp.161-169